How far is too far? Understanding identity and overconformity in collegiate wrestlers - Coker-Cranney, A.; Watson, J. C.; Bernstein, M.; Voelker, D. K.; Coakley, J. (Journal of Quantitative Analysis in Sports, 2018)
Athletes are expected to distinguish themselves from their peers, make sacrifices for the good of the game, play through pain and injury, and push physical and mental limits on the path to achieve their goals. Collectively, these expectations are known as the `sport ethic` and while they are considered part of sport culture, athletes who overconform to them engage in behaviours that pose potentially serious health risks. To explore athlete identity and deviant overconformity, this study was designed within a psychocultural life story framework using a constructivist-interpretivist paradigm. Three Division I wrestlers provided interview data for analysis. Following provisional and narrative coding, a word cloud and creative nonfiction were used to present results. Participants described a process of overconformity to the sport ethic that supported and extended previous research. Results indicated that the participants believed that because athletes must push boundaries in order to find success, they cannot go `too far`. Moreover, they reported that their athlete identity held significant personal and social meaning to the extent that they willingly engaged in forms of deviant overconformity. Recommendations for future research include studies with other sport populations (e.g. other sports, competitive levels, cultural backgrounds) and the development of an instrument to measure athletes` degrees of deviant overconforming. Practitioners may use this research to understand the health-compromising behaviours used by their clients in an effort to obtain athletic success, which may improve treatment planning and outcomes.